Volume 2: Combustion, Fuels and Emissions, Parts a and B 2010
DOI: 10.1115/gt2010-23524
|View full text |Cite
|
Sign up to set email alerts
|

Gaseous and Particulate Emissions Results of the NASA Alternative Aviation Fuel Experiment (AAFEX)

Abstract: The Aircraft Alternative Fuels Emissions experiment (AAFEX) was conducted at National Aeronautic and Space Administration (NASA) Dryden Flight Research Center (DFRC) Aircraft Operations Facility (DAOF) in Palmdale, California, during January and February 2009. The purpose was to systematically investigate the effect of alternative fuels on both gas-phase and particle emissions from a CFM56-2C1 engine on NASA’s DC-8 aircraft parked on the ground as functions of engine power, fuel composition, and exhaust plume … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 7 publications
5
41
0
Order By: Relevance
“…Post-AAFEX 2010 Workshop data [9] also show similar qualitative emissions trends with results herein, yet elude quantitative comparisons for lack of scales on many of the AAFEX reported data.…”
Section: Conclusion: Part Bsupporting
confidence: 61%
“…Post-AAFEX 2010 Workshop data [9] also show similar qualitative emissions trends with results herein, yet elude quantitative comparisons for lack of scales on many of the AAFEX reported data.…”
Section: Conclusion: Part Bsupporting
confidence: 61%
“…All data are from the APEX-3, AAFEX-1, and AAFEX-2 field studies (Bulzan et al 2010). Table 1 lists the relevant experimental details.…”
Section: Field Studiesmentioning
confidence: 99%
“…Timko et al (2010a) provide more detail on the APEX-3 aircraft engines and fuels; their trace gas (Timko et al 2010a;Beyersdorf et al 2012) and PM emissions (Timko et al 2010b) performance have been reported previously. Bulzan et al (2010) and Wey et al (2007) provide more detail on the engine emissions performance of the DC-8 aircraft and its CFM56-2C1 engines used during the AAFEX campaigns. Both APEX-3 and AAFEX used an experimental protocol that has been described previously ).…”
Section: Field Studiesmentioning
confidence: 99%
See 2 more Smart Citations